PERANCANGAN APLIKASI SISTEM SERVICE MOTOR DI PT. MITRA SENDANG KEMAKMURAN - Rustam Effendi; Sutanto Sutanto (LPPM Unbaja, 2020)
Mitra Sendang Kemakmuran Transaction data is still not properly and properly integrated, so it requires a long time in the process of recording transactions and a lack of orderly transaction data storage. Motorcycle Service System Application Design at PT. Mitra Sendang Kemakmuran was created using the Website and Mysql Database programming. The stages of making the system require designing a prototyping method and designing a database system with the concept of UML (Unified Modeling Language). This system can be used multiuser by utilizing technology. This system is designed to make it easier to service and sell spare parts as well as report service data and spare part sales to be faster and more precise.